Temporal coherence patterns of prairie pothole wetlands indicate the importance of landscape linkages and wetland heterogeneity in maintaining biodiversity - McLean, Kyle I.; Mushet, David M.; Sweetman, Jon N. (Frontiers in Ecology and Evolution, 2022)
Wetland ecosystems are diverse, productive habitats that are essential reservoirs of biodiversity. Not only are they home to numerous wetland-specialist species, but they also provide food, water, and shelter that support terrestrial wildlife populations. However, like observed patterns of biodiversity loss, wetland habitats have experienced widespread loss and degradation. In order to conserve and restore wetlands, and thereby the biodiversity they support, it is important to understand how biodiversity in wetland habitats is maintained. Habitat heterogeneity and connectivity are thought to be predominate drivers of wetland biodiversity. We quantified temporal coherence (i.e., spatial synchrony) of wetland invertebrate communities using intra-class correlations among 16 wetlands sampled continuously over 24 years to better understand the relative influences wetland heterogeneity (i.e., internal processes specific to individual wetlands and spatial connectivity (i.e., external processes occurring on the landscape) on wetland biodiversity. We found that while wetlands with different ponded-water regimes (temporarily ponded or permanently ponded) often hosted different invertebrate communities, temporal shifts in invertebrate composition were synchronous. We also found the relative importance of internal versus external forces in determining community assembly vary depending on a wetland’s hydrologic function and climate influences. Our results confirm that heterogeneity and spatial connectivity of wetland landscapes are important drivers of wetland biodiversity.